2007
DOI: 10.1017/s0022215107000412
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular-evoked myogenic potentials and caloric stimulation in infants with congenital cytomegalovirus infection

Abstract: In infants with clinical symptoms of congenital CMV infection present at birth, abnormal vestibular test results occurred more frequently than abnormal auditory brainstem response results. Vestibular organs should be routinely examined in individuals with congenital cytomegalovirus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 27 publications
3
36
0
Order By: Relevance
“…This information can be used to confirm or generate new hypotheses. For example, this study supports the potential link between cCMV and balance problems, 16,17 and suggests a conceivable link between cCMV and autism spectrum disorder, [18][19][20] conditions that are not commonly recognized as being associated with cCMV. It may also be relevant to evaluate the presence of sensory processing disorder and developmental coordination disorder in other cCMV cohorts.…”
Section: Discussionsupporting
confidence: 70%
“…This information can be used to confirm or generate new hypotheses. For example, this study supports the potential link between cCMV and balance problems, 16,17 and suggests a conceivable link between cCMV and autism spectrum disorder, [18][19][20] conditions that are not commonly recognized as being associated with cCMV. It may also be relevant to evaluate the presence of sensory processing disorder and developmental coordination disorder in other cCMV cohorts.…”
Section: Discussionsupporting
confidence: 70%
“…The clinical consequence of these findings are still unknown even though some authors have reported the possibility of carrying out vestibular tests in congenital infected babies [44,46,47]. …”
Section: Resultsmentioning
confidence: 99%
“…The CI group had a larger proportion of children with etiologies that have higher risks for vestibular and balance dysfunctions, such as the Pendred syndrome (Luxon et al 2003), Waardenburg syndrome (Black 1977), CMV infection (Zagólski 2008), and meningitis (Cushing et al 2009) in comparison with the control group whereby the majority had an unknown etiology. Syndromes, such as CMV infection and meningitis, have higher risks for additional subtle neurological deficits that could also impact the balance performance even when the vestibular organ functions optimally.…”
Section: Discussionmentioning
confidence: 99%